Development Of Multimedia Based Learning Media Using Powtoon To Increase Students Learning Interest - Muzayyanah, Ismi Alfi; Asrul; Andhany, Ella (Yana Research, 2022)
This study aims to develop mathematics learning media using Powtoon on set material in class VII SMP IT AL FAKHRI. This research also aims to find out the validity, practicality and effectiveness of the media in increasing students' interest in learning. This type of research is research development or Research and Development which refers to the ADDIE development model which stands for Analysis, Design, Development Implementation and Evaluation. VII grade students of SMP IT AL FAKHRI, totaling 22 people. The instrument used in this research is a validation sheet to measure the validity of the learning media developed by the response questionnaire sheet, the rest of the teacher response questionnaire sheet. The results of the study show (1) the validity of the learning media based on the assessment of media experts is 90% and by material experts is 85% with a very feasible category (2) the practicality of learning media based on the assessment by the teacher is 89% with a very practical category (3) the effectiveness of the media learning based on student learning interest questionnaires using tons obtained 83% with very high or very interested categories.